Lizard survey of Ko Pha-gnan in the Surat Thani Province, Thailand - Dawn Cook-Price; Sunchai Makchai; Archana Naithani; Parinya Pawangkhanant; Pongthep Suwanwaree (Biodiversity Data Journal)
Insular lizard species are under-assessed, rendering them vulnerable to habitat encroachment and other anthropogenic threats. The aim of this study was to compile a comprehensive list of the lizards on Ko Pha-ngan, Thailand. Data were collected via transect surveys, drift line fence traps and opportunistic encounters from January 2021 to October 2023. Three habitat types were surveyed during this period, Than Sadet-Ko Pha-ngan National Park forest, human disturbed forest and human settlement.Our efforts detected a total of 16 lizard species. All species were observed in the national park protected areas, while 12 species in human disturbed forest and seven species in human settlement. Five species (Calotes versicolor, Gekko gecko, Hemidactylus frenatus, Hemidactylus platyurus and Varanus nebulosus) were found in all three habitat types. The two most abundant species detected were C. versicolor and G. gecko. Four species (C. versicolor, G. gecko, Hemidactylus frenatus and Varanus salvator) have exhibited adaptability in human dominated landscapes. Of the species, only one, V. nebulosus is listed as Near Threatened on the International Union for Conservation of Nature Red List of threatened species. The National Park is of growing importance for the survival of the insular species found due to the naturally constricted area of an island. This study sheds light on the need for additional monitoring to better understand the dynamics and the impact tourism-driven development and habitat destruction have on species living in an insularly finite habitat.